Running involvement and life satisfaction: The role of personality. (1st January 2018) - Sato, Mikihiro; Jordan, Jeremy S.; Funk, Daniel C.; Sachs, Michael L.
ABSTRACT: Accumulating evidence suggests that physically active leisure represents an important correlate of life satisfaction; however, the role that personality has on leisure involvement and life satisfaction remains ambiguous. This study explored whether the big-five personality traits explain running involvement and life satisfaction. Participants ( N = 742) were recruited from a distance-running event held in the United States. The results revealed that conscientiousness had positive indirect effects on life satisfaction through attraction, centrality, and self-expression. Openness to experience also had positive indirect effects on life satisfaction through attraction and self-expression. These findings indicate that greater life satisfaction occurs for individuals with high conscientiousness and openness to experience through the enjoyment derived from running and the expression of identity through running.